Calcium signalling regulates the functions of the bZIP protein VIP1 in touch responses in Arabidopsis thaliana. (14th July 2018) - Tsugama, Daisuke; Liu, Shenkui; Fujino, Kaien; Takano, Tetsuo
Abstract: Background and Aims: VIP1 is a bZIP transcription factor in Arabidopsis thaliana . VIP1 and its close homologues transiently accumulate in the nucleus when cells are exposed to hypo-osmotic and/or mechanical stress. Touch-induced root bending is enhanced in transgenic plants overexpressing a repression domain-fused form of VIP1 (VIP1-SRDXox), suggesting that VIP1, possibly with its close homologues, suppresses touch-induced root bending. The aim of this study was to identify regulators of these functions of VIP1 in mechanical stress responses. Methods: Co-immunoprecipitation analysis using VIP1-GFP fusion protein expressed in Arabidopsis plants identified calmodulins as VIP1-GFP interactors. In vitro crosslink analysis was performed using a hexahistidine-tagged calmodulin and glutathione S -transferase-fused forms of VIP1 and its close homologues. Plants expressing GFP-fused forms of VIP1 and its close homologues (bZIP59 and bZIP29) were submerged in hypotonic solutions containing divalent cation chelators, EDTA and EGTA, and a potential calmodulin inhibitor, chlorpromazine, to examine their effects on the nuclear–cytoplasmic shuttling of those proteins. VIP1-SRDXox plants were grown on medium containing 40 mm CaCl2, 40 mm MgCl2 or 80 mm NaCl. MCA1 and MCA2 are mechanosensitive calcium channels, and the hypo-osmotic stress-dependent nuclear–cytoplasmic shuttling of VIP1-GFP in the mca1 mca2 double knockout mutant background was examined. Key Results: In vitro crosslink products were detected in the presence of CaCl2, but not in its absence. EDTA, EGTA and chlorpromazine all inhibited both the nuclear import and the nuclear export of VIP1-GFP, bZIP59-GFP and bZIP29-GFP. Either 40 mm CaCl2 or 80 mm NaCl enhanced the VIP-SRDX-dependent root bending. The nuclear–cytoplasmic shuttling of VIP1 was observed even in the mca1 mca2 mutant. Conclusions: VIP1 and its close homologues can interact with calmodulins. Their nuclear–cytoplasmic shuttling requires neither MCA1 nor MCA2, but does require calcium signalling. Salt stress affects the VIP1-dependent regulation of root bending.